GE11 Peptide Conjugated Liposomes for EGFR-Targeted and Chemophotothermal Combined Anticancer Therapy - Xueqin Huang; Lingzhi Chen; Yuping Zhang; Suyan Zhou; Huai-Hong Cai; Ting Li; Hua Jin; Jiye Cai; Haibo Zhou; Jiang Pi (Bioinorganic Chemistry and Applications)
How to actively target tumor sites manipulating the controllable release of the encapsulated anticancer drugs and photosensitizers for synergistic anticancer therapy remains a big challenge. In this study, a cancer cell-targeted, near-infrared (NIR) light-triggered and anticancer drug loaded liposome system (LPs) was developed for synergistic cancer therapy. Photosensitizer indocyanine green (ICG) and chemotherapy drug Curcumin (CUR) were coencapsulated into the liposomes, followed by the surface conjugation of GE11 peptide for epidermal growth factor receptor (EGFR) targeting on the cancer cell surface. Strictly controlled by NIR light, GE11 peptide modified and CUR/ICG-loaded LPs (GE11-CUR/ICG-LPs) could introduce hyperthermia in EGFR overexpressed A549 cancer cells for photothermal therapy, which could also trigger the increased release of CUR for enhanced cancer cell inhibition. GE11-CUR/ICG-LPs synergized photochemotherapy could induce reactive oxygen species (ROS) generation and cytoskeleton disruption to activate stronger apoptotic signaling events than the photothermal therapy or chemotherapy alone by regulating Bax/Bcl-2 and PI3K/AKT pathways. This EGFR-targeted drug-delivery nanosystem with NIR sensitivity may potentially serve in more effective anticancer therapeutics with reduced off-target effects.